Leisure marketing : a global perspective - Horner, Susan (Elsevier Butterworth-Heinemann, 2005)
Divided into nine parts, Leisure Marketing: a global perspective guides the reader through leisure and marketing concepts, the marketing mix, key issues in different sectors, topical issues (such as globalisation, marketing research and ethics, for example branding and environmental issues), and the future of leisure marketing. A section of the book is devoted entirely to international case studies, which illustrate and highlight key themes and issues raised throughout in order to facilitate learning. Example of international cases used are: *Disneyland Resort, Paris: The Marketing Mix *Manchester United Football Club: Marketing the Brand *The Growth of the Online Retail Travel Market *Hilton Head Island, USA: The Leisure Island for Golf and Leisure Shopping *Health, Leisure and Tourism Marketing including Spa Hotels, Health Clubs and lake Resorts. * International case studies to facilitate understanding * Concentrated and comprehensive study of leisure marketing * Uses real life events to highlight key themes and issues such as marketing of sports stadia as multi purpose venues, leisure retailing: from designer outlets to markets, and corporate hospitality in sport.